The effects of reward systems in prison: A systematic review. (December 2022) - Elbers, Jan Maarten; van Ginneken, Esther F.J.C.; Nieuwbeerta, Paul; Boone, Miranda; Palmen, Hanneke
Abstract: Introduction: Using rewards to influence behavior and attitudes of incarcerated individuals is historical, widespread, and becoming increasingly popular. Surprisingly, little is known on the effectiveness of reward systems in prison (RSPs). This paper aims to address this gap. Method. A systematic review on RSPs was conducted, twenty one studies met the inclusion criteria. Results. Overall, findings on RSP effectiveness were mixed. Three study types were identified. Type-1 studies indicated that experimental RSPs using tokens yield positive short-term behavioral effects in individuals cognitively functioning below average. Type-2 studies indicated that non-experimental RSPs are most successful when targeting high-risk participants and include cognitive program elements. Type-3 (qualitative) studies highlight three potential moderators: a pain of self-government, perceived legitimacy, and using family contact as a reward. Discussion. As overall study quality is below average, findings should be interpreted with caution. Results were partially congruent with prior research. Highlights: Dated studies report positive effects of the use of rewards in prison on behavior. Recent studies report mixed effects on the use of rewards in prison on behavior. Contemporary reward systems in prison are effective for high-risk participants. Contemporary reward systems in prison are effective when targeting cognitive change. Implementation factors can mediate system effectiveness, such as perceived legitimacy.